Knowledge and Attitude of self-medication with leftover antibiotics in Saudi Arabia: A cross-sectional study [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Saad Alsubaie; Omar Al-Morikhi; Bader Al-Mehmadi; Saud Alenazi; Khalid Alanazi; Maryam Al-Mutairi; Mohammed Alotaibi; Fawaz Alqahtani; Waad Almutairi (F1000Research)
Background Antimicrobial resistance is increasing at an alarming rate. The use of antibiotics without a prescription by a patient or other family members and their inappropriate storage have caused serious health issues as it would lead to antibiotic resistance and exposure to the risk of harmful adverse effects unnecessarily. Therefore, the study aimed to evaluate the current behaviour of antibiotic usage, storage, re-usage and misuse among the residents of Saudi Arabia. Methods This is a cross-sectional study. Our target study population was the residents of Saudi Arabia. Data were collected by an online questionnaire and analysed by SPSS. Results A total of 738 participants answered the online questionnaire from all ages, genders, nationalities, and socioeconomic backgrounds residing in different regions across the Kingdom of Saudi Arabia. 76.42% knew that an antibiotic is a chemical substance used to treat infections. The participants were questioned about when they started using antibiotics, to which 95.66% (n=706) responded after consulting a physician, 3.25% (n=24) said when they felt ill for any reason, and 1.08% (n=8) replied after first attempting herbal medicine. A total of 147 participants admitted that they store excess pills of antibiotics after being prescribed for an infection and reuse them later on for symptoms like sore throat and fever. Conclusions The results indicated that nearly half of the participants used leftover antibiotics. Participants having children in their homes significantly reuse antibiotics. However, one-third of the participants didn’t complete the antibiotics course. A large portion of the population, regardless of age, level of education, or professional background, have continued to store leftover antibiotics after an infection treatment and reuse them once they think they need them for new symptoms. This advice further revises the current measures to fill those gaps and reduce this habit.